International collaboration: official visit from the Faculty of Medicine, Universitas Hasanuddin to the Department of Rehabilitation Medicine, Hospital Al-Sultan Abdullah - Zainudin, Muhamad Faizal; Ngimron, Anie Farhana; Ahmad Roslan, Nor Faridah; Omar, Mazlifah; Mohamad Hashim, Natiara; Hanapiah, Fazah Akhtar (Faculty of Medicine, 2023)
On the crisp Wednesday morning of July 12th, 2023, the Department of Rehabilitation Medicine warmly received an eminent delegation from Universitas Hasanuddin (UNHAS), Sulawesi, Indonesia. This international rendezvous aligned with the continuous commitment in the Memorandum of Understanding (MoU) ratified in August 2022. The MoU was a significant agreement between the Faculty of Medicine, UNHAS, and the Faculty of Medicine, Universiti Teknologi MARA (UiTM).